Optimization Of Poverty Reduction Through Human Development Index Schemes And Indirect Spending At Belitung Regency - Setiadi, Ade Dwi; Mafruhat, Ade Yunita (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
Poverty is a problem that national governments have always faced, namely developed and developing countries' local governments. Several factors causing poverty were selected, including the Indirect Spending and Human Development Index, which was studied to influence poverty in Belitung Regency. The purpose of the study is to optimize poverty reduction through the Human Development Index and Indirect Spending scheme in the short and long term in Belitung Regency in 2011-2021, using secondary data from the website of the Central Statistics Agency (BPS). The method used Error Correction Model (ECM) and processed using Eviews. The results of data processing in this study show that Indirect Spending and human development indices negatively affect poverty in the short and long